Textile Dye Decolorization Potential of Bacillus pumilus and Staphylococcus saprophyticus Isolated From Textile Industry Effluents (Bangladesh Journal of Microbiology, 2024)
Textile dyeing industries are usually chastised for being big polluters due to the poisonous nature of most dyes, which endangers all kinds of life, including people. In this study, dye degrading bacteria were isolated from water and soil samples contaminated with textile dye taken from Batik palli in Narayanganj and the ability of five isolated bacteria including Staphylococcus saprophyticus, Bacillus pumilus, Micrococcus endophyticus, Pseudomonas mendocina, and Acinetobacter baumannii, to decolorize crystal violet (CV) dye was investigated. Among these, Bacillus pumilus decolorized 58% of CV at 250 ppm, while Staphylococcus saprophyticus decolorized 48% of CV, after 3 days of incubation at 37°C. We examined multiple temperature and pH conditions to determine the best parameters for CV dye decolorization. Bacillus pumilus boosted decolorization rates by 65.39% at 37°C and at pH 7.0, while Staphylococcus saprophyticus increased decolorization rates by 58.73%, at 37°C and at pH 5.0. Furthermore, extending the incubation period to 6 days enhanced decolorization rate in both isolates, with Bacillus pumilus increased from 58% to 65% and Staphylococcus saprophyticus increased from 48% to 58%. Nevertheless, the inclusion of co-substrates such glucose and yeast extract further boosting decolorization rate for both isolates, approximately tripling it. As a result, this study discovered indigenous bacteria capable of decolorizing CV dye, implying that they could be employed in the treatment of textile wastewater effluents.Bangladesh J Microbiol, Volume 40, Number 2, December 2023, pp 50-54